The Usefulness of Hybrid Security Classifications: Evidence from Redeemable Preferred Stock. - Kimmel, Paul; Warfield, Terry D. (The Accounting Review, 1995)
Presents empirical evidence on the economic substance of the hybrid security redeemable preferred stock (RPFD). Variation in the relation between firm leverage and systematic risk; RPFD's impact on systematic risk; Factors affecting market perception of RPFD.